A multidimensional cohort study of late toxicity after intensity modulated radiotherapy for sinonasal cancer. (October 2020) - Sharma, Maja Bendtsen; Jensen, Kenneth; Urbak, Steen Fiil; Funding, Mikkel; Johansen, Jørgen; Bechtold, Dorte; Amidi, Ali; Eskildsen, Simon Fristed; Jørgensen, Jens Otto Lunde; Grau, Cai
Highlights: Late toxicity is substantial in all examined organs at risk. Associations between dose to the optic nerve and ocular toxicity was present. Across all examinations, 74% had late toxicity in more than one organ. The severity of toxicity increased with increasing number of organs affected. Abstract: Purpose: To evaluate the occurrence of late toxicity after curatively intended intensity modulated radiotherapy (IMRT) for sinonasal cancer and assess dose–response associations. Methods: Patients treated with IMRT in 2008–2016 were included. Cross sectional examinations of toxicity from the optic pathway, the brain, the pituitary gland and the nose were performed along with quality of life – (QoL) and dose–response analyses. Results: Twenty-seven patients were enrolled; median age was 67 years (range 47–83). Five patients (19%) had radiation-related ocular toxicity. The risk of visual acuity impairment increased with increasing dose (grade 2 odds ration (OR) 1.12, p  = 0.01; grade 3 OR 1.14, p  = 0.02) and dose constraint violations (grade 2, OR = 21, p  < 0.01; grade 3, OR = 41, p  < 0.01). Six patients (22%) exhibited evidence of radiation-related hypopituitarism, but no dose–response association was detected. Seventeen patients (63%) had impaired olfactory function. The risk of olfactory impairment increased with higher stage (OR = 3.32, p  = 0.03) . Three patients (11%) had structural abnormalities in irradiated areas of the brain, and impaired cognitive function was present in 17 patients (63%). Cognitive, physical, role functioning as well as fatigue and insomnia were affected the most in QOL analyses. Fifteen patients (56%) had grade 2 radiation-related impairment in at least one organ. Grade 3 toxicity was only present in patients with toxicities in >3 organs and in patients initially treated for T4 tumours. Three patients (11%) had radiation-related impaired function in all examined OARs. Conclusion: Late toxicity after radiotherapy was substantial in all examined organs, with dose–response associations between visual acuity impairment and the optic nerve. The results have led to changed praxis for follow-up examinations in Denmark.